Admixture mapping of ankle–arm index: identification of a candidate locus associated with peripheral arterial disease. Issue 1 (7th July 2009) - Scherer, M L; Nalls, M A; Pawlikowska, L; Ziv, E; Mitchell, G; Huntsman, S; Hu, D; Sutton-Tyrrell, K; Lakatta, E G; Hsueh, W-C; Newman, A B; Tandon, A; et al.
Abstract : Background: Peripheral arterial disease (PAD) is associated with significant morbidity and mortality, and has a higher prevalence in African Americans than Caucasians. Ankle–arm index (AAI) is the ratio of systolic blood pressure in the leg to that in the arm, and, when low, is a marker of PAD. Methods: The authors used an admixture mapping approach to search for genetic loci associated with low AAI. Using data from 1040 African American participants in the observational, population based Health, Aging, and Body Composition Study who were genotyped at 1322 single nucleotide polymorphisms (SNPs) that are informative for African versus European ancestry and span the entire genome, we estimated genetic ancestry in each chromosomal region and then tested the association between AAI and genetic ancestry at each locus. Results: The authors found a region of chromosome 11 that reaches its peak between 80 and 82 Mb associated with low AAI (p<0.001 for rs12289502 and rs9665943, both within this region). 753 African American participants in the observational, population based Cardiovascular Health Study were genotyped at rs9665943 to test the reproducibility of this association, and this association was also statistically significant (odds ratio (OR) for homozygous African genotype 1.59, 95% confidence interval (CI) 1.12 to 2.27). Another candidate SNP (rs1042602) in the same genomic region was tested in both populations, and was also found to be significantly associated with low AAI in both populations (OR for homozygous African genotype 1.89, 95% CI 1.29 to 2.76). Conclusion: This study identifies a novel region of chromosome 11 representing an area with a potential candidate gene associated with PAD in African Americans.